Nationalism, Democratisation and Primordial Sentiment in Indonesia: Problems of Ethnicity versus Indonesianness (the cases of Aceh, Riau, Papua and Bali) - Irine Hiraswari Gayatri (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2010)
-